THE CORRELATION BETWEEN STUDENTS’ WATCHING ENGLISH MOVIE AND THEIR READING ACHIEVEMENT OF CLASS X SMAN 2 LAWE SIGALA GALA - Roslinda, Erba; Lumban Raja, Viator; Prayuda, Meikardo Samuel (Kairos English Language Teaching Journal, 2022)
The aim of this study is to find out the correlation between Watching English Movie and Their Reading Achievement of Class X SMA N 2 Lawe Sigala gala. this research is quantitative research. The data of the research were examined by using Pearson Product Moment Correlation. The data were statistically computed through the Statistical Package for Social Science (SPSS) 23. The result of this research showed that there is a significant correlation between Watching English Movie and Their Reading Achievement of Class X SMA N 2 Lawe Sigala gala. Based on the rtable of Pearson Product Moment Coefficient above, it could be seen that rtable at the significant level 5% is 0,279. It could be concluded that rxy (0,539) is higher that rtable at the significant 5%. It means that Ho is rejected. Therefore, it can be concluded that there is a significant correlation between Watching English Movie and Their Reading Achievement of class X SMA N 2 Lawe Sigala gala. this implies that if one has high Reading, it can be predicted that he will also have a high Watching English Movie.